PKM Prototype Alat Kontrol Pengaman Listrik pada Gedung/Rumah Berbasis Relay Raspberry bagi Guru dan Siswa SMKT Somba Opu Kabupaten Gowa - Syarifuddin Kasim; Yunus Tjandi (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract. The installation of electricity and control devices that are not in accordance with PUIL’s standards will cause huge losses for consumers. This Community Associate Program aims to : (1) Broaden knowledge of students and teachers of Somba Opu Vocational School to build electric safety control software for buildings based on raspberry relay, (2) Improve skills of students and teachers of Somba Opu Vocational School to build electric safety control software, (3) Improve skills and knowledge of associate in order to be able to provide solutions of problems faced at Somba Opu Vocational School, Gowa. The method used in this workshop training are lecturer, discuss, debrief, and demonstration. The result shows that : (1) community’s knowledge of build a control and monitoring electric safety device for buildings based on raspberry relay has increased, (2) community’s knowledge enhanced by utilizing and build electric safety control device based on rapsberry relay, (3) Have skills and knowledge in order to provide solutions of problems faced at Somba Opu Vocational School, Gowa.